2023
DOI: 10.3390/pathogens12010080
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathogenic and Opportunistic Oral Bacteria in Early Life: The Role of Maternal Factors in a Portuguese Population

Abstract: In early life, maternal factors are of the utmost relevance for oral microbiome acquisition and maturation. Therefore, our study explored the impact of maternal factors, such as saliva and breastmilk colonization, cardiovascular risk factors (CRF), type of delivery, oral health, and caregiving habits on the prevalence of potential pathogenic and opportunistic oral bacteria in early life. A total of 26 healthy mothers, 23 mothers with CRF, and their 50 children were included and samples (child’s oral swabs, mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Recently, our research group has suggested a potential relevant role of the mother in bacterial vertical transmission to the child and this study has confirmed this to fungi [ 48 ]. Within the limitations of this study, we hypothesize that delivery may be the initial event for fungal vertical transmission, with the transfer of the fungi present on the skin or in vagina and perianal region to the mouth and, subsequently, gut of the child, which may then be perpetuated by breastfeeding and close contact with the mother.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, our research group has suggested a potential relevant role of the mother in bacterial vertical transmission to the child and this study has confirmed this to fungi [ 48 ]. Within the limitations of this study, we hypothesize that delivery may be the initial event for fungal vertical transmission, with the transfer of the fungi present on the skin or in vagina and perianal region to the mouth and, subsequently, gut of the child, which may then be perpetuated by breastfeeding and close contact with the mother.…”
Section: Discussionsupporting
confidence: 71%
“…Among non-communicable diseases, ECC is the first consequence of sugar consumption and can affect children even before completing the first year of life [ 18 20 ]. Parental level of education is associated with offering sugar in the first year of life [ 18 , 26 ] and early introduction of mature oral bacteria [ 27 ] both of which are important factors associated with ECC. However, little is known about the pathways by which parental education may affect the risk for ECC.…”
Section: Introductionmentioning
confidence: 99%